Oppikirja musiikkisemiotiikasta - Lång, Markus (Tieteessä tapahtuu, 2003)
Eero Tarasti: Signs of Music: A Guide to Musical Se miotics. Approaches to Applied Semiotics, 3. Mouton de Gruyter, Berlin. 2002. 224 s.